INTRASENTENTIAL AND INTERSENTENTIAL CODE SWITCHING IN INDONESIAN MODERN LITERATURE METROPOP “DENGAN HATI” - UMMI RASYIDAH (English Study Program University of Pasir Pengaraian, 2015)
ABSTRACTThis study aimed at examining the types and the function of codes switching found in Indonesian Modern Literature Syafrina Siregar‟s novel „Dengan Hati‟. A review of related literature in code switching were provided for the analysis of the data. The data were taken from the conversation among the characters in this novel. This study is categorized as descriptive qualitative with content analysis. The finding showed that intersentential are dominantly used. While the function of code switching referred to cultural identity.